Efektivitas Pelayanan Publik Di Kantor Kelurahan Tanjung Selor Timur Kecamatan Tanjung Selor Kabupaten Bulungan - Abdul, Kartini Maharani; Mulyadi, Budi; Kirana, Andhika Putra (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to find out how effective public services are at the East Tanjung Selor Village office in Tanjung Selor District, Bulungan Regency. This research is qualitative and uses primary and secondary data. There were eight informants used. Observation, interview, and documentation are methods used to collect data. Data analysis techniques include the process of data collection, data condensation, data presentation, and verification of conclusions. Source trigulation ensures data validity. According to the research results, even though there are shortcomings, the Tanjung Selor Timur Kelurhan office in Tanjung Selor District Bulungan Regency has effective public services, if seen from the point of view (1) service procedures are considered effective, (2) completion time has been considered effective, (3) Service costs have been considered efficient, (4) facilities and infrastructure have been considered effective despite deficiencies, (5) employee competence is already considered effective, (6) service products have been considered effective.